(untitled) (Iranian Journal of Kidney Diseases, 2013)
Primary sarcomas of kidney are rare tumors accounting for 1% to 3% of all primary renal malignancies. Among sarcomas fibrosarcoma is rare. Here we report a case of primary fibrosarcoma of the kidney in a 70-year-old man who presented with gradually increasing abdominal swelling and pain.